Evaluating tetracycline degradation pathway and intermediate toxicity during the electrochemical oxidation over a Ti/Ti4O7 anode. (15th June 2018) - Wang, Jianbing; Zhi, Dan; Zhou, Hao; He, Xuwen; Zhang, Dayi
Abstract: Tetracycline (TC) is one of the most widely used antibiotics with significant impacts on human health and thus it needs appropriate approaches for its removal. In the present study, we evaluated the performance and complete pathway of the TC electrochemical oxidation on a Ti/Ti4 O7 anode prepared by plasma spraying. Morphological data and composition analysis indicated a compact coating layer on the anode, which had the characteristic peaks of Ti4 O7 as active constituent. The TC electrochemical oxidation on the Ti/Ti4 O7 anode followed a pseudo-first-order kinetics, and the TC removal efficiency reached 95.8% in 40 min. The influential factors on TC decay kinetics included current density, anode-cathode distance and initial TC concentration. This anode also had high durability and the TC removal efficiency was maintained over 95% after five times reuse. For the first time, we unraveled the complete pathway of the TC electrochemical oxidation using high-performance liquid chromatograph (HPLC) and gas chromatograph (GC) coupled with mass spectrometer (MS). ·OH radicals produced from electrochemical oxidation attack the double bond, phenolic group and amine group of TC, forming a primary intermediate ( m/z  = 461), secondary intermediates ( m/z  = 432, 477 and 509) and tertiary intermediates ( m/z  = 480, 448 and 525). The latter were further oxidized to the key downstream intermediate ( m/z  = 496), followed by further downstream intermediates ( m/z  = 451, 412, 396, 367, 351, 298 and 253) and eventually short-chain carboxylic acids. We also evaluated the toxicity change during the electrochemical oxidation process with bioluminescent bacteria. The bioluminescence inhibition ratio peaked at 10 min (55.41%), likely owing to the high toxicity of intermediates with m/z  = 461, 432 and 477 as obtained from quantitative structure activity relationship (QSAR) analysis. The bioluminescence inhibition ratio eventually decreased to 16.78% in 40 min due to further transformation of TC and intermediates. By comprehensively analyzing the influential factors and complete degradation pathway of TC electrochemical oxidation on the Ti/Ti4 O7 anode, our research provides deeper insights into the risk assessment of intermediates and their toxicity, assigning new perspectives for practical electrochemical oxidation to effectively eliminate the amount and toxicity of TC and other antibiotics in wastewater. Graphical abstract: Highlights: Satisfactory tetracycline degradation (95.8%) on a Ti/Ti4 O7 anode. The tetracycline electrochemical oxidation follows a pseudo-first order kinetics. First complete pathway of tetracycline electrochemical oxidation. Toxicity evaluation of 25 intermediates by QSAR explains toxicity reduction delay.